Evaluation of Growth Response of Superwin Rice Variety to Salinity at The Germination Phase - Billy Deivico Manis; Susan Marlin Mambu; Song Ai Nio (Jurnal Ilmiah Sains, 2023)
Evaluation of the salinity resistance of Superwin as a local rice of North Sulawesi, is still very limited. This study aimed to examine the growth response of Superwin compared with Ciherang variety to various levels of seawater salinity at the germination phase. The research commenced with planting rice seeds using the Roll Paper Test method, then growing them under salinity treatments of 0, 10, and 20% seawater. The observed rice growth responses were the percentage of germination, the length of seminal root and shoot, the ratio of seminal root length: shoot length and the vigor index. The results of analysis of variance (ANOVA) showed that the percentage of germination, the length of seminal root and shoot, and vigor index were significantly different between two varieties and among salinity treatments. The interaction between factors of variety and salinity treatment caused differences in the ratio of seminal root length: shoot length. Superwin showed higher percentage of germination, the length of seminal root and shoot as well as vigor index than Ciherang. The 0% and 10% salinity treatments showed a higher percentage of germination, the length of seminal root and shoot as well as vigor index than the 20% treatment. The ratio of seminal root length and shoot length was a potential indicator of salinity stress in Superwin rice. Keywords: Germination; rice; salinity; superwin